2004
DOI: 10.1300/j015v27n01_10
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Attitudes Toward Counseling as Predictors of Biracial College Women's Psychological Help-Seeking Behavior

Abstract: This study explored the extent to which biracial college women's attitudes toward counseling and reported depressive symptoms would predict their psychological help-seeking behavior. Results of a logistic regression analysis revealed that biracial college women with more favorable attitudes toward counseling were more likely to seek professional psychological help. In addition, biracial women with higher depression scores were more likely to seek professional mental health treatment. Implications of the findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The growth in visibility of this population suggests that counselors will see increasing numbers of multiracial clients (Constantine & Gainor, 2004). Although dealing with society's reactions to being racially mixed may not be the main reason that a client seeks counseling, it is still important for clinicians to be knowledgeable of the salient issues that might affect these clients' daily lives as a result of their dual heritage (Edwards & Pedrotti, 2004b;Nishimura, 2004;Pedrotti, Edwards, & Lopez, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The growth in visibility of this population suggests that counselors will see increasing numbers of multiracial clients (Constantine & Gainor, 2004). Although dealing with society's reactions to being racially mixed may not be the main reason that a client seeks counseling, it is still important for clinicians to be knowledgeable of the salient issues that might affect these clients' daily lives as a result of their dual heritage (Edwards & Pedrotti, 2004b;Nishimura, 2004;Pedrotti, Edwards, & Lopez, 2008).…”
mentioning
confidence: 99%
“…growing population of multiracial individuals who are likely to seek counseling (Constantine & Gainor, 2004), this dearth of published research in counseling journals is concerning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Parslow and Jorm (2000) found that characteristics like age and education level might also contribute to the decision for men to seek-help from professionals. The revelation that gender roles play a part in decision to utilize psychological services is similar to previous literature examining differences in help-seeking behavior of men and women, male gender roles, and the relationship between openness to services and expectations in the general population (e.g., Good, 1995;Constantine & Gainor, 2004).…”
Section: Social Influence and Gender Rolessupporting
confidence: 70%
“…This finding may also reflect the type of baseball coach who selected into participating in the study. Although previous research has demonstrated large gender differences between men and women with regards to help-seeking behavior, openness to psychological services, and general acceptance and understanding for psychology (e.g., Constantine & Gainor, 2004;Good, 1995), it would be impossible to determine differences in the current study since close to 100% of participants in the current study were male. Coaching jobs at the high school, collegiate, and professional level usually require at least bachelor's degree; it would also make sense that the majority of participants have graduated from college.…”
Section: General Demographic Informationmentioning
confidence: 78%